(untitled) - Ghobadian, Abby (New York, N.Y., 2004)
Few current issues in public management are as controversial as public-private partnerships (PPPs). The intensity of the debate reflects the importance of the concept to the government as it focuses on its central policy objective of improving public services, and the degree of opposition that is ranged against it. Opinion is divided with alternative views emerging across the political spectrum. Private Public Partnerships presents a fresh and wide-ranging review of the core issues behind the debate, capturing the experiences and insight of practitioners at the forefront of the first wave of PPP programs, research and analysis from leading academics who have studied the performance of PPPs, and critical views from advocates and opponents of the concept.
Keywords: Public-private sector cooperation,Privatization,Public-private sector cooperation,Privatization; Great Britain,Great Britain